Hard magnetic and broadband microwave absorption characteristics of heat-treated Pr15-XDyXFe77B8(x = 0, 1, 2, and 3) alloys. Issue 9 (September 2022) - Sudrajat, Nanang; Taryana, Yana; Dedi, Dedi; Ari Adi, Wisnu; Darmawan, Lucky; Manaf, Azwar
Abstract: In this study, fabrication of Pr15-x Dyx Fe77 B8 (at.%) alloys with x = 0, 1, 2, and 3 compositions was performed with a mini vacuum arc melting furnace. The alloys were successively annealed in an inert atmosphere for microstructure homogenization. All alloys exhibit the typical characteristics of a permanent magnet. The coercivity gradually increases with increasing atomic fraction of Dy. The heat treatment applied to the samples changed the properties from those of a permanent magnet to those of a microwave absorber. The reflection loss (RL) value evaluated by a Vector Network Analyzer (VNA) shows broadband absorption characteristics in the full 8 GHz–12 GHz frequency range. The RL and bandwidth increase with the addition of the Dy substitute. The as-cast and annealed Pr15- x Dyx Fe77 B8 alloy with the x = 1 composition shows superior absorption, starting from the 8 GHz frequency and increasing progressively, reaching less than -17 dB or an absorption of more than 85.0 % at a peak frequency of 10.5 GHz, after which it weakens to -6 dB at a frequency close to 12 GHz. Heat-treated samples were characterized by absorption with two almost overlapping absorption peaks at frequencies of 9.5 GHz and 11.5 GHz, leading to very broadband absorption across the full frequency range (8–12 GHz). It is concluded that permanent magnetic materials could be converted into radar absorbing materials (RAM). RAM based on heat-treated rare earth permanent magnet has broadband absorption characteristics. Graphical abstract: Image 1 Abstract : Rare-earth; Permanent magnets; Anisotropy field; Reflection loss; Radar absorbing materials.